Clube União Beneficente: o protagonismo pedagógico de um clube social negro no município de São Vicente do Sul/RS - Jobim, Letícia Mossate (2013)
This research have the comprehension‟s purpose of the character what a negro social group at São Vicente‟s city/Rs-Brazil handled here like a pedagogic contrivance exerted in cultural and identifier process happen in another group that have had experiences about to be negro . This way, how the researched group realizes him into social context and what categories arrange his speeches given meaning to it. The theoretical approach is in Cultural studies using methodological techniques by Hybrid and Themes of Oral History and it was used minutes, documents and photos. From recurrences of narratives was determined what analysis‟s categories that discussed about these themes: The regulation‟s behavior that provides utmost visibility and admission of Negro in the society; The production of identify and apathy and to know such as they are set in motion through Social group like contrivance; The relation‟s exercises between to be able/to know; The ambiguity of color‟s speeches and the negotiation this speeches; The introduction of the pedagogic racial; and The hybridism that typified the Union club. The results of research found with this contrivance shaped by dynamic bailiwick of negotiations, adjustments, regulations, changes and alliances. It was evidenced that doesn‟t absolute true about Negro‟s culture and unique narratives too, but speeches, impersonations and social practices that vary according to the moments with are subjected.